SPE-UPLC-MS/MS assay for determination of letrozole in human plasma and its application to bioequivalence study in healthy postmenopausal Indian women - Pravin G. Vanol; Puran Singhal; Priyanka A. Shah; Jaivik V. Shah; Pranav S. Shrivastav; Mallika Sanyal (Elsevier, 2016)
A rapid and sensitive ultra performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) method is described for determination of letrozole in human plasma. Following solid phase extraction (SPE) of letrozole and letrozole-d4 on Orochem DVB-LP cartridges, chromatography was performed on Acquity UPLC BEH C18 (50 mm×2.1 mm, 1.7 µm) column using methanol-0.1% formic acid in water (85:15, v/v) as the mobile phase. Detection was carried out on a triple quadrupole mass spectrometer with an electrospray source, operated under positive ionization mode. Quantitation of letrozole and letrozole-d4 was done using multiple reaction monitoring (MRM) following the transitions at m/z 286.2→217.0 and m/z 290.2→221.0, respectively. The calibration plots were linear through the concentration range of 0.10-100 ng/mL (r2≥0.9990) using 100 µL human plasma. The extraction recovery of letrozole ranged from 94.3% to 96.2% and the intra-batch and inter-batch precision was ≤5.2%. The method was successfully applied to a bioequivalence study of letrozole after oral administration of 2.5 mg tablet formulation to 16 healthy postmenopausal Indian women. The assay reproducibility was also established through incurred sample reanalysis (ISR) of 74 subject samples.